(untitled) (Biological Sciences - PJSIR, 2003)
I.D.fan (Kiln) of a Cement plant consisting of a motor, two mechanical couplings, a hydraulic coupling and a heavy fan (approx. two tons) was giving high vibrations at some locations. This was monitored at all the bearing locations and its vibration symptoms were recorded for analysis purpose. Frequency domain and phase analysis were made to diagnose the root cause of vibrations. On the basis of this analysis, fault observed was mainly with the fluid coupling. The vibration spectra and phase data are presented in this paper.